El Cuestionario de Salud General de Goldberg (GHQ-28): Una revisión sistemática - Ames Guerrero, Rita (2024)
In order to facilitate the understanding of tools that monitor general health, we developed a systematic review of the Goldberg General Health Questionnaire (GHQ-28) to determine the risk factors that explain the psychological problems that were identified in the general population. Previously, a bibliometric approach was carried out to identify research trends on the scientific literature of the GHQ-28. We use Web of Science and Scopus as information sources to retrieve scientific production on GHQ-28, from 2016 and 2021 in English and Spanish. We retrieved 45 studies obtained by search equations, including only 33 systematic review studies after applying the inclusion and exclusion criteria. A massive increase in post-covid-19 pandemic mental health problems was identified, being reported using the GHQ-28 instrument. Common risk factors are identified that inform mental health deterioration. The instrument is useful for the early identification of symptoms and the formulation of prevention and intervention programs in favor of the mental health of the human population.